Apocrine secretion in the salivary glands of Drosophilidae and other dipterans is evolutionarily conserved - Babišová, Klaudia; Mentelová, Lucia; Geisseová, Terézia Klaudia; Beňová-Liszeková, Denisa; Beňo, Milan; Chase, Bruce A.; Farkaš, Robert (Frontiers in Cell and Developmental Biology, 2023)
We recently demonstrated that, in Drosophila melanogaster, the prepupal salivary glands utilize apocrine secretion prior to pupation to deliver innate immune and defense components to the exuvial fluid that lies between the metamorphosing pupae and its chitinous case. This discovery provided a unique opportunity to appraise how this novel non-canonical and non-vesicular transport and secretory mechanism is employed in different developmental and evolutionary contexts. Here we demonstrate that this apocrine secretion, which is mechanistically and temporarily separated from the exocytotic mechanism used to produce the massive salivary glue secretion (Sgs), is shared across Drosophilidae and two unrelated dipteran species. Screening more than 30 species of Drosophila from divergent habitats across the globe revealed that apocrine secretion is a widespread and evolutionarily conserved cellular mechanism used to produce exuvial fluid. Species with longer larval and prepupal development than D. melanogaster activate apocrine secretion later, while smaller and more rapidly developing species activate it earlier. In some species, apocrine secretion occurs after the secretory material is first concentrated in cytoplasmic structures of unknown origin that we name „collectors“. Strikingly, in contrast to the widespread use of apocrine secretion to provide exuvial fluid, not all species use exocytosis to produce the viscid salivary glue secretion that is seen in Drosophila melanogaster. Thus, apocrine secretion is the conserved mechanism used to realize the major function of the salivary gland in fruitflies and related species: it produces the pupal exuvial fluid that provides an active defense against microbial invasion during pupal metamorphosis.